4CPS-254 Biosimilar rituximab – a year beyond. (March 2019) - Pereira, M; Costa, G; Domingos-Camões, S; Alcobia, A
Abstract : Background: The introduction of a biosimilar drug represents similar efficacy at lower cost, providing savings without compromising patient treatment. In oncology, biological therapies account for more than 33% of health expenses. 1 Rituximab has a particular profile of first infusion-related reactions (IRR), such as hypersensitivity reactions, hypotension and cardio-respiratory compromise, which may lead to treatment discontinuation. 2 Purpose: To evaluate the safety profile of biosimilar rituximab in the approved indications and the economic impact of the introduction of biosimilar rituximab. Material and methods: Retrospective analysis of first IRR reported to the pharmacy services or described in the patient file with biosimilar rituximab, between July 2017 and July 2018. The switch to biosimilar rituximab was performed in all patients. Results: During the analysis period, 127 patients had been treated with biosimilar rituximab. According to their pathology, they were classified into two categories: oncological, 48% and non-oncological disorders, 52%, which included rheumatoid arthritis (RA) and off-label use. In the oncological group, the switch was carried out in 9.8% of patients, 90.2% were naïve. The mean time between the last administration of rituximab and the first administration of biosimilar rituximab was 34 days [(21–58 days). Three suspension cases of biosimilar rituximab have been reported, resulting in two successful re-challenges and one permanent discontinuation. The rate of first IRR was 6.5% in oncological disorders, with three severe reactions (4.9%). Regarding the non-oncological group, the switch was performed in 39.4% of patients, 60.6% were naïve. The mean switch time was 13.6 months (0.9–48 months). One case of suspension was reported, which resulted in a successful re-challenge. The rate of first IRR was 2.9% for RA, with no severe reactions. Biosimilar rituximab introduction translated into a 64% cost reduction of €1 71 000. Conclusion: Biosimilar rituximab introduction resulted in significant savings (64%) with no major changes in safety profile (4.5% oncological disorders and none for RA of severe first IRR), when compared with the summary of product characteristics of the originator (12% and 0.5%). 2 The difference may be associated with an underestimated report, since it is a commonly used drug with a known IRR profile. References and/or acknowledgements: 1. http://www.infarmed.pt/documents/15786/2682984/junho/34525a26–4c19–4035–8132-cfdb29105022?version=1.0 2. Mabthera SPC available at: https://www.ema.europa.eu/documents/product-information/mabthera-epar-product-information_en.pdf No conflict of interest.